Evidence Against an Important Role of Plasma Insulin and Glucagon Concentrations in the Increase in EGP Caused by SGLT2 Inhibitors - Alatrach, Mariam; Laichuthai, Nitchakarn; Martinez, Robert; Agyin, Christina; Ali, Ali Muhammed; Al-Jobori, Hussein; Lavynenko, Olga; Adams, John; Triplitt, Curtis; DeFronzo, Ralph; Cersosimo, Eugenio; Abdul-Ghani, Muhammad (Diabetes (New York, N.Y.), 2020)
Sodium–glucose cotransport 2 inhibitors (SGLT2i) lower plasma glucose but stimulate endogenous glucose production (EGP). The current study examined the effect of dapagliflozin on EGP while clamping plasma glucose, insulin, and glucagon concentrations at their fasting level. Thirty-eight patients with type 2 diabetes received an 8-h measurement of EGP ([3-3H]-glucose) on three occasions. After a 3-h tracer equilibration, subjects received 1) dapagliflozin 10 mg (n = 26) or placebo (n = 12); 2) repeat EGP measurement with the plasma glucose concentration clamped at the fasting level; and 3) repeat EGP measurement with inhibition of insulin and glucagon secretion with somatostatin infusion and replacement of basal plasma insulin and glucagon concentrations. In study 1, the change in EGP (baseline to last hour of EGP measurement) in subjects receiving dapagliflozin was 22% greater (+0.66 ± 0.11 mg/kg/min, P < 0.05) than in subjects receiving placebo, and it was associated with a significant increase in plasma glucagon and a decrease in the plasma insulin concentration compared with placebo. Under glucose clamp conditions (study 2), the change in plasma insulin and glucagon concentrations was comparable in subjects receiving dapagliflozin and placebo, yet the difference in EGP between dapagliflozin and placebo persisted (+0.71 ± 0.13 mg/kg/min, P < 0.01). Under pancreatic clamp conditions (study 3), dapagliflozin produced an initial large decrease in EGP (8% below placebo), followed by a progressive increase in EGP that was 10.6% greater than placebo during the last hour. Collectively, these results indicate that 1) the changes in plasma insulin and glucagon concentration after SGLT2i administration are secondary to the decrease in plasma glucose concentration, and 2) the dapagliflozin-induced increase in EGP cannot be explained by the increase in plasma glucagon or decrease in plasma insulin or glucose concentrations.